Quem faz uma rádio comunitária? Estudo de caso em uma favela da Zona Oeste do Rio de Janeiro - Vives, Regina Celia Azevedo (2009)
The present study intends to offer the ways to understanding of the functioning of the radios in the favela Rio das Pedras, located in the neighborhood of Jacarepaguá, in the city of Rio de Janeiro, and the knowledge concerning the joint of the community concept of radio reproduced by the involved actors in the radios transmissions. The development of the research on the radios of this favela was favored by the participant comment in the field, that a friendly environment for accomplishment of the interviews of history of life of the owner of the radios, allowing the understanding of its relations with the radio community, objective, future expectations of the broadcasting in the locality, and still the establishment of an analytical synthesis of the relations between the speeches produced by the owner of theses radios.